2010
DOI: 10.3109/01421590903394603
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in communication skills training in UK schools of medicine

Abstract: While the paper identifies and delineates a typical or 'modal' model of CST in UK Schools of Medicine, it also emphasizes the importance of flexibility in this part of the curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 7 publications
1
34
0
1
Order By: Relevance
“…In a review of communication skills training (Aspegren 1999), experiential methods were reported to be more effective in teaching communication skills than instructional methods. Nowadays experiential methods such as SPs and RP are widely used in communication skills training (Lane & Rollnick 2007;Cleland et al 2009;May et al 2009;Hargie et al 2010). SPs portray live interactive simulations of specific communication challenges and medical problems, offering the students a safe learning environment with no risk of harm to real patients (Kurtz et al 2005).…”
Section: )mentioning
confidence: 99%
“…In a review of communication skills training (Aspegren 1999), experiential methods were reported to be more effective in teaching communication skills than instructional methods. Nowadays experiential methods such as SPs and RP are widely used in communication skills training (Lane & Rollnick 2007;Cleland et al 2009;May et al 2009;Hargie et al 2010). SPs portray live interactive simulations of specific communication challenges and medical problems, offering the students a safe learning environment with no risk of harm to real patients (Kurtz et al 2005).…”
Section: )mentioning
confidence: 99%
“…4 Communication training and teaching tools such as the Calgary Cambridge framework 5 are integral components of undergraduate medical curricula and general practice training. 6,7 Although models provide a framework for teaching and learning, throughout undergraduate medical training and continuing into general practice training, emphasis is placed on learning to implement a variety of communication skills in differing situations. 8 Learners are not restricted to the confines of one rigid checklist, but are taught to develop their own consulting style and to adapt or combine elements of different models to suit both clinical context, patients' needs, and clinicians' individual preferences.…”
Section: Introductionmentioning
confidence: 99%
“…) Vuorovaikutusopintojen sisäl lyttäminen lääketieteen perustutkintoon ei kui tenkaan ole ongelmatonta. Ongelmia aiheuttavat ajan puute jo muutenkin täydessä opetussuun nitelmassa ja opetushenkilökunnan ristiriitaiset asenteet vuorovaikutusopintoja kohtaan (32,33). Lääkäripotilasvuorovaikutustutkimuksen tulos ten soveltaminen opetuksen tarpeita vastaavasti ja oppimismenetelmien kehittäminen on osoit tautunut vaikeaksi tehtäväksi (28).…”
Section: Sosiaalilääketieteellinen Aikakauslehti 2017: 54: 134-150unclassified